Benefits of pallidal stimulation in dystonia are linked to cerebellar volume and cortical inhibition. Issue 1 (December 2018) - Fečíková, Anna; Jech, Robert; Čejka, Václav; Čapek, Václav; Šťastná, Daniela; Štětkářová, Ivana; Mueller, Karsten; Schroeter, Matthias; Růžička, Filip; Urgošík, Dušan
Abstract Clinical benefits of pallidal deep brain stimulation (GPi DBS) in dystonia increase relatively slowly suggesting slow plastic processes in the motor network. Twenty-two patients with dystonia of various distribution and etiology treated by chronic GPi DBS and 22 healthy subjects were examined for short-latency intracortical inhibition of the motor cortex elicited by paired transcranial magnetic stimulation. The relationships between grey matter volume and intracortical inhibition considering the long-term clinical outcome and states of the GPi DBS were analysed. The acute effects of GPi DBS were associated with a shortening of the motor response whereas the grey matter of chronically treated patients with a better clinical outcome showed hypertrophy of the supplementary motor area and cerebellar vermis. In addition, the volume of the cerebellar hemispheres of patients correlated with the improvement of intracortical inhibition which was generally less effective in patients than in controls regardless of the DBS states. Importantly, good responders to GPi DBS showed a similar level of short-latency intracortical inhibition in the motor cortex as healthy controls whereas non-responders were unable to increase it. All these results support the multilevel impact of effective DBS on the motor networks in dystonia and suggest potential biomarkers of responsiveness to this treatment.